How Do Flies Walk Upside Down - Berger, Melvin; Nang Chan Yeema (New York, USA Scholastic Inc., 1999)
A Series of questions and answers provides information about the physical characteristics, senses, eating habits, life cycles, and behavior of different insects.
Keywords: Juvenile Nonfiction